Gene Expression Profiling for Cardiac Rejection Surveillance is not Predictive of Post‐Transplantation Skin Cancer. Issue 10 (1st October 2013) - Hanlon, Allison; O'Neill, Megan; Fang, Fiona; Chen, Heidi; Lott, Jason; Wigger, Mark; Stasko, Thomas
<x xml:space="preserve">Abstract</x> Background The risk of skin cancer in solid organ transplant recipients (SOTR) is 50 to 100 times as great as in those without a transplant. Multiple factors, including immunosuppression, influence the development of post‐transplantation skin cancer. Individuals with cardiac transplant are serially screened for organ rejection and immunosuppressive regimen effectiveness. Gene expression profiling of peripheral blood mononuclear cells has been established as a noninvasive test for monitoring cardiac rejection. Objective We examined individuals with cardiac transplant monitored using peripheral gene expression profiling to determine whether the profile of peripheral blood mononuclear cell activity could correlate with the development of post‐transplantation skin cancer. Methods and Materials Sixty‐one patient records were examined for initial endomyocardial biopsy results, gene expression profiling data, immunosuppressive regimens, and post‐transplantation skin cancer. Results There was no relationship between acute rejection and the development of skin cancer. No relationship between peripheral gene expression profiling and the development of post‐transplantation skin cancer was observed. The most common skin cancer in the population was squamous cell carcinoma. SOTR suppressed with azathioprine had a significantly higher incidence of squamous cell carcinoma. Conclusion Although gene expression tests have advanced transplant surveillance, they were not associated with post‐transplantation skin cancer.